2020
DOI: 10.3390/antibiotics9090556
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of the World Health Organization Health Care Facility-Based Antimicrobial Stewardship Toolkit for Low- and Middle-Income Countries

Abstract: Antimicrobial stewardship (AMS) has emerged as a systematic approach to optimize antimicrobial use and reduce antimicrobial resistance. To support the implementation of AMS programs, the World Health Organization developed a draft toolkit for health care facility AMS programs in low- and middle-income countries. A feasibility study was conducted in Bhutan, the Federated States of Micronesia, Malawi, and Nepal to obtain local input on toolkit content and implementation of AMS programs. This descriptive qualitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 16 publications
(20 reference statements)
0
28
0
Order By: Relevance
“…We previously reported that the lack of enforcement of policies and guidelines from the MoH and hospital administration remains a significant barrier to ASP adoption and implementation [ 7 ]. This barrier has also been highlighted in Maki et al’s 2020 study [ 31 ]. MOH hospitals are clearly expecting the MOH to enforce the adoption, implementation and regular monitoring of ASPs in its hospitals.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…We previously reported that the lack of enforcement of policies and guidelines from the MoH and hospital administration remains a significant barrier to ASP adoption and implementation [ 7 ]. This barrier has also been highlighted in Maki et al’s 2020 study [ 31 ]. MOH hospitals are clearly expecting the MOH to enforce the adoption, implementation and regular monitoring of ASPs in its hospitals.…”
Section: Discussionmentioning
confidence: 70%
“…Alternative ASP implementation models have been suggested to address this challenge [ 28 , 29 , 30 ]. Senior management in Saudi hospitals is supportive of the adoption of ASPs and implementation; this is a key facilitator, as reported in Maki et al’s feasibility study [ 31 ], to ensure resource allocation, and ASP monitoring and evaluation. Senior managers’ support needs to extend beyond the “no objection to implementation” stance, to actively secure the necessary funds, skills and expertise to implement ASPs.…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions have been shown to improve knowledge of pharmacovigilance [ 50 ] and prescribing competency [ 51 ] as well as to strengthen AMS [ 52 , 53 , 54 ], although the effects may be short-lived. Online learning as part of AMS programmes has been playing an increasing role [ 55 ] and online training of GPs has been shown to reduce antimicrobial prescribing for respiratory disease [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 In creation of the toolkit, interviews were undertaken in order to evaluate the feasibility of the toolkit within LMIC. 50 Input was gathered from national leaders, health care facility leadership, and health care facility staff. This input was then incorporated into the toolkit to ensure the most usability.…”
Section: Creating An Antimicrobial Stewardship Programmentioning
confidence: 99%
“…During the feasibility studies of the WHO AMS toolkit, it was noted that strong leadership support at the national and senior facility management levels was needed for successful implementation. 50 The WHO AMS toolkit is a resource for facilities within LMIC to create a strong AMS program and serves as a reference to continue to build on structures put in place, such as current IPC committees, in an effort to continue to control the development and spread of AMR. 18…”
Section: Creating An Antimicrobial Stewardship Programmentioning
confidence: 99%